2015
DOI: 10.1002/oby.21121
|View full text |Cite
|
Sign up to set email alerts
|

Association of body fat composition and obstructive sleep apnea in the elderly: A longitudinal study

Abstract: Objective: Obesity and aging are considered risk factors for developing sleep apnea syndrome (OSA). The aim of this study was to determine the association between body fat composition and OSA in healthy elderly subjects examined in a 7-year longitudinal study. Methods: A total of 209 elderly with unrecognized OSA aged 68.3 6 0.8 years underwent a clinical, ambulatory nocturnal respiratory recording, and anthropometric as well as body fat composition assessment by dual-energy X-ray absorptiometry (DEXA) at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
3
9
0
3
Order By: Relevance
“…Previous studies showed the lack of an association between central fat mass effect and OSA in elderly patients. 28 This finding was confirmed by our results. Other studies using BIA demonstrated a relationship between the severity of neck fluid volume of water and the severity of SDB.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed the lack of an association between central fat mass effect and OSA in elderly patients. 28 This finding was confirmed by our results. Other studies using BIA demonstrated a relationship between the severity of neck fluid volume of water and the severity of SDB.…”
Section: Discussionsupporting
confidence: 90%
“…Fat mass, especially around the neck and abdomen, contribute to increased AHI and worsening hypoxemia. 25,26 The associations between reduced HGS in both dominant and non-dominant hands and worsening hypoxemia indices, being T90% and O2 nadir, with the addition of mean desaturation when whole body fat mass is not adjusted for, confirms previous finding showing those who spent more than 1% of the night with oxygen saturation below 90% had significantly weaker grip strength compared to those who did not. 13 Likewise, no association was detected between HGS and AHI, which is also in line with previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore better characterization of body fat distribution rather than reliance upon the BMI and anthropometry is necessary to define obesity and its impact on OSA. Novel methods to characterize fat deposition such as dual energy X‐ray absorptiometry (DEXA) imaging have begun to be used …”
Section: Biomarkers Of Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Novel methods to characterize fat deposition such as dual energy X-ray absorptiometry (DEXA) imaging have begun to be used. [18][19][20] New objective biomarkers are necessary for OSA. Future investigations should consider biomarkers of hypoxic stress or arousal, central ventilatory control and sleep homeostasis.…”
Section: Biomarkers Of Obstructive Sleep Apnoeamentioning
confidence: 99%